Impact of Financial Literacy, Income, and Lifestyle On The Financial Behavior of Accounting Students In Surabaya - Khamdi, Muhammad Afif; Sundari, Siti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze how financial literacy, income, and lifestyle influence the financial behavior of accounting students at state universities in Surabaya. Methodology: A quantitative, correlational research design was applied, with 100 respondents selected using Slovin’s formula and simple random sampling. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). Results: The study found that financial literacy, income, and lifestyle all significantly and positively influence students' financial behavior. Findings: Financial literacy, income, and lifestyle play critical roles in shaping the financial behavior of students, emphasizing the importance of financial education. Novelty & Originality: This study contributes to the literature by highlighting the roles of financial literacy, income, and lifestyle in influencing students' financial behavior, focusing on Surabaya, an under-researched area. Conclusion: Improving financial literacy and fostering a frugal lifestyle can significantly enhance financial decision-making among students. Type of Paper: Empirical Research